Small To Medium Enterpirses In The Digital Era On Line Shop Professional Community (Kaji) In East Java - Idham, Idham; Made, Henni; Dewi Fitrianingsih, Sri; Bin Mukhtar, Dzulkifli (International Journal of Science, Technology & Management, 2024)
Small To Medium Enterpirses In The Digital Era On Line Shop Professional Community (Kaji) In East Java. The contribution of SMEs has had an impact on the regional and national economy (Bunga, 2022), the growth and development of SMEs in Indonesia cannot be separated from the various challenges faced, the economic crisis that occurred at the end of 1997 brought multi-economic impacts, including SMEs (Tejasari, 2008), the impact of Covid 19 which occurred in early 2020, the impact of the global economy occurred as a whole. SMEs also felt the same impact with the independence that SMEs have, being able to overcome global economic challenges (Aksan, 2022), entering the digital era. East Java UKM (KAJI) is faced with online shop UKM must be able to take a role and control the market so that the existence of SMEs is not eroded by digitalization, especially online shops. Legitimacy theory focuses on interactions between companies and society based on legitimacy theory, namely that a "social contract" occurs between companies and the community where the company operates and uses economic resources. It explains the concept of social contract, all social institutions, including companies, operate in society through social contracts, both explicit and implicit, their survival and growth is based on what consists of, the final result (social output) provided to the wider community, the distribution of economic, social and political benefits. to groups according to their power (Gray, 2001). The research method used in the research is qualitative analysis of case studies. Single case case study is used to obtain data from various primary and secondary research sources (observations, artifacts, archives, documents, interviews, multiple sources), is a research strategy involving one or more cases (multi cases) creating theoretical constructions, middle range propositions or theories based on empirical fact cases (Eisenhardt, 1989). The results of the research and discussion can be concluded that the existence of East Java UKM (KAJI) is described as follows: a. Able to support the family economy as an alternative source of family income, b. The existence of KAJI East Java, facilitates UKMs to establish friendly relations between UKMs, c. Market opportunities are still limited. SMEs still have difficulty marketing SME products. e. The attention received by SMEs in business development and capital assistance has not been maximized, f. Lack of innovation and creativity among SMEs. Suggestions for the existence of SMEs should receive more attention, especially in policies that support the existence of SMEs, especially the policy of implementing online shops to ensure the continuity of the existence of SMEs.